A new and practical carbon paste electrode for insoluble and ground samples - Almeida, CMVB; Giannetti, B. F. (Elsevier B.V., 2002)
This work presents a new and simple electrode, which may be used to achieve the electrochemical response of ground solids or insoluble samples. Ore samples from Morro Velho Mine (Brazil) were employed to exemplify the use of such electrodes. The new electrode avoids the use of binders or other agents overcoming major deterioration problems. (C) 2002 Published by Elsevier Science B.V.
Keywords: carbon paste electrodes; ground minerals; electrochemical response